Variabilidad de hibradación interespecífica - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
During 1984 several types of interspecific crosses between Phaseolus vulgaris and P. coccineus, generated in the collaborative project with the U. of Gembloux, Belgium, were tested to evaluate their yield potential. Significant differences were observed between the crosses tested and among sister lines for traits such as yield, disease resistance, vigor, plant architecture, raceme length, seed size and color. Also, 3 successive generations (C3 to C5) of the tetraploid hybrid P. acutifolius x P. vulgaris were grown in the field at CIAT-Palmira; resistance close to immunity to bacterial blight was identified in the cross G 40034 x Bico de Ouro. In Rio Negro (Colombia), a P. coccineus multiplication nursery was established which involved 330 accessions from the P. coccineus collection for evaluation and seed multiplication. (CIAT)